Trace Minerals, Vitamins and Nutraceuticals in Prevention and Treatment of COVID-19. (22nd April 2022) - Srivastava, Ajay; Gupta, Ramesh C.; Doss, Robin B.; Lall, Rajiv
Abstract: Coronavirus disease 2019 (COVID-19) was first officially diagnosed in the city of Wuhan, China in January 2020. In reality, the disease was identified in December 2019 in the same city where patients began showing symptoms of pneumonia of unidentified origin. Very soon the disease became a global pandemic due to the suppression of information in the country of origin and inadequate testing for the COVID-19 virus. Currently, > 101 million people have been found positive for this virus and > 2.17 million people have died. There are no signs that COVID-19 is slowing down. This deadly virus affects multiple vital organs (lungs, heart, nervous system, blood, and immune system), yet its exact mechanism of pathophysiology remains obscure. Depending on the viral load, sick people often show symptoms of fever, cough, shortness of breath, coagulopathy, cardiac abnormalities, fatigue, and death. Great strides have been made in COVID-19 testing, thereby allowing timely therapeutic intervention. Currently, vaccines are on the market from Pfizer, Moderna and Astra Zeneca with limited supply. Phase III clinical trials are also underway from other manufacturers. In the current scenario, nutraceuticals and other phyto-mineral supplements appear to be promising alternative solutions for the prevention and treatment of COVID-19.